Early Child Development and Parents' Labor Supply - Lukáš Lafférs; Bernhard Schmidpeter (Institute of Labor Economics (IZA), 2020)
The impact of children's early development status on parental labor market outcomes is not well established in the empirical literature. We combine an instrumental variable approach to account for the endogeneity of the development status with a model of non- random labor force participation to identify its impact. A one unit increase in our poor child development index reduces long-term maternal weekly hours worked by 9 hours and weekly income by 215 Australian Dollars. We provide evidence that mothers substitute working time with childcare to compensate for early disadvantages. We do not find any responds of fathers to early child development.
Keywords: C21; I23; J13; J31; J64; 330; child development; maternal labor supply; sample selection; instrumental variables estimation; time use